Effects of dulaglutide combined with insulin degludec on glucose fluctuations and appetite in type 2 diabetes - Huang, Jinxin; Hua, Fei; Jiang, Xiaohong; Zhang, Xingguang; Yang, Minxing; Wang, Long; Huang, Xiaolin; Luo, Kaiming (Frontiers in Endocrinology, 2023)
Introduction The aim of this study was to describe appetite and glucose fluctuation in type 2 diabetes mellitus patients initiating treatment with dulaglutide combined with insulin degludec. Methods This retrospective study of patients identified adults starting treatment with once-weekly (QW) dulaglutide combined with insulin degludec (experimental group) or insulin degludec alone (control group). Patients were followed for up to 6 months from treatment initiation. The clinical characteristics of patients, treatment patterns, CGM data, and appetite scores were obtained for the two groups. Results A total of 236 patients were included in this study. SDBG, MAGE, LAGE, and PPGE of the experimental group were lower than the control group’s (P < 0.05). The proportions of patients achieving a time in range (TIR) of ≥70% in the experimental group were higher than in the control group, with 43% and 10% on the second day, 88% and 47% on the fourth day, 95% and 47% on the seventh day, and 100% and 67% on the tenth day, respectively. Significant associations existed between TIR and the prevalence of islet function. At six months, 89.2% of patients in the experimental group were still using dulaglutide. Appetite decreased significantly at 1 week and increased at 3 months after treatment with dulaglutide. Conclusion Dulaglutide combined with insulin degludec significantly reduces glucose fluctuations in patients with type 2 diabetes mellitus and improves the TIR rate. However, the treatment on appetite could decrease in the first three months.